Prevalence and risk factors of sub-health and circadian rhythm disorder of cortisol, melatonin, and temperature among Chinese midwives - Chen, Xiao-Qian; Jiang, Xiu-Min; Zheng, Qing-Xiang; Wang, Hai-Wei; Xue, Heng; Pan, Yu-Qing; Liao, Yan-Ping; Gao, Xiao-Xia (Frontiers in Public Health, 2023)
Objective: To explore the influencing factors of sub-health and circadian rhythm disorder among midwives, as well as whether circadian rhythm disorder was associated with sub-health. Methods: A multi-center cross-sectional study was conducted among 91 Chinese midwives from 6 hospitals through cluster sampling. Data were collected by demographic questionnaire, Sub-Health Measurement Scale Version 1.0 and circadian rhythm detection. Minnesota single and population mean cosine method were used to analyze the rhythm of cortisol, melatonin and temperature. Binary logistic regression, nomograph model and forest plot was performed to identify variables associated with midwives’ sub-health. Results: There were 65 midwives with sub-health and 61, 78, 48 midwives with non-validation of circadian rhythms of cortisol, melatonin, temperature among 91 midwives, respectively. Midwives’ sub-health was significantly related to age, duration of exercise, weekly working hours, job satisfaction, cortisol rhythm, melatonin rhythm. The nomogram, based on these 6 factors, was presented with significant predictive performance for sub-health. Furthermore, cortisol rhythm was significantly associated with physical, mental and social sub-health, whereas melatonin rhythm was significantly correlated with physical sub-health. Conclusion: Sub-health and circadian rhythm disorder were generally common among midwives. Nurse administrators are supposed to pay attention and take measures to prevent sub-health and circadian rhythm disorder among midwives.